RHETORIC WRITTEN IN THE HEADLINE OF MARKET ISSUES: A CRITICAL DISCOURSE ANALYSIS - Rina Mulya .; Sumarsih . .; I Wayan Dirgeyasa (LINGUISTIK TERAPAN, 2023)
In the age of accessible news, where it can be obtained anywhere and anytime, news can be shared through social media, and it merely showed the headline as the way to intrigue the readers. The writing of headline structures expressed what is the center of information, who is the participant, and what action is done. This issue unintentionally can also shape the readers’ perception, the order of participants and action in the sentence influence the various aspect into the meaning. This study examined how rhetoric is written in the headlines of market issues based on critical discourse analysis. It applied the theory proposed by Van Dijk (2013) namely formal structures of discourse.  300 data were obtained from November 2022 to February 2023 based on the syntactic structures. The findings showed that there are three ways that media used in arrangement of words and phrases to create the headline news. They are active, passive, and nominalizations. Active become the most types used in the headline, followed by passive and nominalizations. This analysis inferred that the perspective of CNBC Indonesia is neutral but sometimes they also supported the government's economic policies. It is because they did not show their inclination towards one party.